Dear Girl, - Rosenthal, Amy Krouse; Rosenthal, Paris (Harper, an imprint of HarperCollinsPublishers, 2017)
Encourages readers to accept and love themselves as they are and advises them to be confident, curious, adaptable, and willing to speak up.